Effects of Shenfu Injection (参附注射液) on Inflammatory Response during Post-Resuscitation Myocardial Dysfunction after Cardiac Arrest in Swine - Gu, Wei (Chin J Integr Med, 2021)
OBJECTIVE: To investigate whether Shenfu Injection (SFI, 参附注射液) can alleviate post-resuscitation myocardial dysfunction by inhibiting the inflammatory response. METHODS: After 8 min of ventricular fibrillation and 2 min of basic life support, 24 pigs were randomly divided into 3 groups (n=8), which were given intravenous bolus injections of SFI (1.0 mL/kg), epinephrine (EP, 0.02 mg/kg) and normal saline (SA), respectively. The animals were sacrificed at 24 h after restoration of spontaneous circulation (ROSC), and serum interleuking-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels were measured by enzyme-linked immunosorbent assay (ELISA); expressions of Toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) mRNAs and proteins were determined by RT-PCR and Western blot, respectively. RESULTS: Compared with the EP and the SA groups, the ultrastructure of myocardial cells were slightly damaged and the systolic function of the left ventricle was markedly improved in the SFI group at 24 h after ROSC (P<0.05). In addition, compared with the EP and SA groups, the SFI group also showed significantly reduced levels of serum IL-6 and TNF-α, protein and mRNA levels of myocardial NF- κB and TLR4 (P<0.05). CONCLUSIONS: Activation of TLR4/NF-κB signaling pathway may be involved in the pathological mechanisms of post-resuscitation myocardial dysfunction. SFI may block NF-κB-mediated inflammatory response by reducing the activity of NF- κB and the level of TNF-α, thus playing a protective role in post-resuscitation myocardial dysfunction.